2020
DOI: 10.2118/194158-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Casing-Pipe Roughness on Cement-Plug Integrity

Abstract: Summary In permanently abandoned wells, cement plugs serve as a well-barrier element that is essential for providing long-term zonal isolation. Poorly plugged wells might provide leakage pathways that pose risks to the surrounding environment. It is well-known that the final quality of set cement is influenced by the cement placement, but the influence of downhole-pipe roughness to the hydraulic sealing of a cement plug has not been specifically investigated. This paper presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The specific volumes of the cracks and microannuli were extracted using Avizo and imported into StarCCM+ [61] for computational fluid flow (CFD) simulations as described in references [45,[50][51][52]. The surface was manually repaired to maintain the structural features of the geometries.…”
Section: Simulation Of Fluid Flowmentioning
confidence: 99%
See 4 more Smart Citations
“…The specific volumes of the cracks and microannuli were extracted using Avizo and imported into StarCCM+ [61] for computational fluid flow (CFD) simulations as described in references [45,[50][51][52]. The surface was manually repaired to maintain the structural features of the geometries.…”
Section: Simulation Of Fluid Flowmentioning
confidence: 99%
“…Stormont et al [24] and Garcia Fernandez et al [25] found experimentally that the microannulus aperture can vary considerably around the circumference when they studied gas flow through different microannuli, and concluded that microannuli have complex geometries. For simplicity however, a common approach in many studies is to assume microannuli uniformity, which for example, works well when converting measured fluid flow rates to microannuli apertures by introducing the terms "equivalent" or "effective" microannulus [20,[68][69][70]. A limitation of this approach is that the estimated microannuli sizes are not really correct and give no accurate information about the actual microannuli geometry [9,50].…”
Section: Visualization Of Microannuli and Cement Debondingmentioning
confidence: 99%
See 3 more Smart Citations